An Advanced Backcross Population through Synthetic Octaploid Wheat as a “Bridge”: Development and QTL Detection for Seed Dormancy - Dale, Zhang; Jie, He; Luyu, Huang; Cancan, Zhang; Yun, Zhou; Yarui, Su; Suoping, Li (Frontiers in Plant Science, 2017)
The seed dormancy characteristic is regarded as one of the most critical factors for pre-harvest sprouting (PHS) resistance. As a wild wheat relative species, Aegilops tauschii is a potential genetic resource for improving common wheat. In this study, an advanced backcross population (201 strains) containing only Ae. tauschii segments was developed by means of synthetic octaploid wheat (hexaploid wheat Zhoumai 18 × Ae. tauschii T093). Subsequently, seed dormancy rate (Dor) in the advanced backcross population was evaluated on the day 3, 5 and 7, in which 2 major QTLs (QDor-2D and QDor-3D) were observed on chromosomes 2D and 3D with phenotypic variance explained values (PVEs) of 10.25% and 20.40%, respectively. Further investigation revealed significant correlation between QDor-3D and Tamyb10 gene, while no association was found between the former and TaVp1 gene, implying that QDor-3D site could be of closer position to Tamyb10. The obtained quantitative trait locus sites (QTLs) in this work could be applied to develop wheat cultivars with PHS resistance.